Academic staff in Europe : changing contexts and conditions - Enders, Jürgen (Greenwood studies in higher education., 2001)
Annotation Higher education is going through a turbulent period of change. In this work, distinguished experts from fourteen European countries highlight recent developments that affect today's academic environment. Based on a research project coordinated by Junger Enders at the University of Kassel in Germany, the book higlights the changes taking place in higher education.